Cancun update : review of the dispute settlement understanding (International Centre for Trade and Sustainable Development GenevaCH, 2003)
Notes the prospects for Cancun. Provides a background to the topic and looks at the current state of play.
Keywords: TRADE NEGOTIATIONS